Cosets and Lagrange's Theorem Quotient Groups

Cosets and Lagrange's Theorem Quotient Groups

Quotient Groups Surjective Group Homomorphisms Examples Cosets and Lagrange's theorem If G is a group and H is a subgroup we may dene a left coset to be a subset xH = xh h H : f j 2 g Proposition 1. Any two left cosets are either equal or disjoint. Each has cardinality H . j j Corollary 2. (Lagrange's theorem) If H is a subgroup G = H [G: H] where the index [G: H] is dened to be the number of left cosets. j j j j Quotient Groups Let G be a group with a normal subgroup N. (Notation: N G) The denition of normality is: g G gNg 1 = N: P 2 ) ¡ Often useful to check (explained Monday) if g G gNg 1 N 2 ) ¡ 1 this is sucient to imply normality. Reminder: we may replace g by g¡ in the last inclusion and g G g 1Ng N 2 ) ¡ g 1Ng N N gNg 1: ¡ ) ¡ Combine this with gNg 1 N give gNg 1 = N. ¡ ¡ Some subgroups are normal, some are not. For example in S3 the subgroups of order 2 are not normal but the unique subgroup (123) = A3 is normal. If X, Y are subsets of G dene h i XY = xy x X; y Y : f j 2 2 g We have (XY )Z = X(YZ) because both sides equal xyz x X ; y Y ; z Z : f j 2 2 2 g Theorem 3. Let G/N be the set of left cosets xN of the normal subgroup N. The product of two cosets is a coset and G/N is a group (called the quotient group). More precisely: 1 1 (xN)(yN) = xyN ; (xN)¡ = x¡ N The coset N = 1 N serves as the identity in G/N. Proof. The boxed equation is the main thing to check. The identity 1 gNg¡ = N can be written gN = Ng: To prove (xN)(yN) = xyN: xNyN = xyNN = xyN: 1 1 xNx¡ N = xx¡ N = N and it is also easy to see N (xN) = (xN)N = xN so the coset N serves as an identity. Look at the boxed equation (xN)(yN) = xyN This means we have a map : G G/N dened by (x) = xN. This equation shows that is a homorphism. It is su¡r!jective since by denition every element of G/N is a coset xN = (x). Surjective group homomorphisms Theorem 4. Let G and Q be groups and : G Q a surjective group homomor- phism. Let ¡! K = ker( ) = x G (x) = 1 : f 2 j g This is a normal subgroup. Then G = Q K : j j j j j j Proof. Dene an equivalence relation on G: x y if (x) = (y): Since surjective, the number of equivalence classes is equal to Q . Indeed, a typical equivalence class equals j j C(q) = x G (x) = q ; q Q: f 2 j g 2 Dummit and Foote use the term ber. What I will show is that the equivalence classes are cosets of K. Let x G and let q = (x). I claim that y x if and only if y xK. In other words 2 2 C(q) = xK: To prove this, rst assume y xK, say y = xk with k K. Then 2 2 (y) = (xk) = (x) (k) = (x)1 = (x) = q so y C(q). This proves that xK C(q). Conversely assume that y C(q). Then 2 1 2 (y) = q. Let k = x¡ y. We have 1 1 1 (k) = (x¡ y) = (x)¡ q = q¡ q = 1 so k K. Thus y = xk xK proving C(q) xK. Combining this with our previous inclu2sion C(q) = xK. 2 The number Q of bers equals the number of coset xK. By Lagrange's theorem, this equals [G: Kj] ajnd G = K [G: K] = K Q : j j j j j jj j Example We've seen that S4 has a normal subgroup of order V , the Klein 4-group: V = 1; (12)(34); (13)(24); (14)(23) : f g We'll make a group action of S4 on a set with 3 elements. Let X = (12)(34); (13)(24); (14)(23) f g And S will act on this set by conjugation. If g S and x X then gxg 1 X. 4 2 4 2 ¡ 2 1 2 3 4 g = a b c d then 1 2 3 4 a b c d g (12)(34)g 1 = (12)(34) = (ab)(cd) ¡ a b c d 1 2 3 4 shows that conjugating an element of shape (xy)(zw) gives an element of the same shape. (I haven't defined shape but appeal to your intuition.) This shows that 1 gXg¡ X and both sets have same cardinality so they are equal. The proof that V is normal uses the same calculation. Recall from Lecture 3 1 that if I have a action of G on a set X I have a homo- morphism G Sym(X) (the set of permutations of X, denoted SX in DF). If X is as above X ¡=!3 so I get a homomorphism G S . j j ¡! 3 Lemma 5. This homomorphism is surjective. Proof. If g G let (g) Sym(X) be the corresponding permutation. Label: 2 2 A = (12)(34); B = (13)(24); C = (14)(23): g = (12) 1 gAg¡ = (12)(12)(34)(12) = (12)(34) = A 1 gBg¡ = (12)(13)(24)(12) = (14)(23) = C 1 gCg¡ = (12)(14)(23)(12) = (13)(24) = B So ((12)) = (BC): Similarly (13) = (AC). Now Sym(X) = S3 is generated by the two transpositions (BC) and (AC). Since (G) contains a set of generators of S3 it equals S3 so is surjective. By the theorem, G = ker( ) S , in other words 24 = ker( ) 6 and so j j j j j 3j j j ker( ) = 4: j j Observe that V is abelian so it acts trivially by conjugation on X V . Therefore V ker( ). Both have order 4 and so V = ker(y). .

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    4 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us